Phenomenological Study: Construction of Cultural Meaning in Madurese Coffee Traders - Asydiqul Fanju; Nawang Sukma Ayuningtyas; Yhesika Pramudiani (Journal of Social Science, 2023)
Informal economy in the sector of street vendors or street vendors nowadays has become the job many choose to reap the coffers of profits. One of the many choices is trading coffee. The profits obtained can make or build economic independence for business actors or actors. This study discusses the cultural meaning of wandering among Madurese coffee traders to know the reasons behind the wandering of Madurese coffee traders. From another point of view, trading coffee for Madurese coffee traders is not only done to fulfill their daily needs, but there is a cultural construction behind their efforts to orient themselves towards other individuals. Because of its continuity, social relations bind and certainly contribute to the success of its business. Social relations, in this case, are the actor's involvement with the Madurese culture of migrating and orientation in efforts to fulfill the needs of his family's life. The method used in this research is qualitative. This research was conducted employing observation and interviews from sources related to the meaning of wandering among Madura coffee traders. This research describes the description of an actor who is required to face a new social reality to change his destiny, as well as the condition of the Madurese land, which requires most of its people to migrate. The theory in analyzing this research is Maximilian Weber's theory of social action theory. This theory is used in analyzing the rational actions of actors through the construction of their ethnic culture.